2019
DOI: 10.2337/db17-0821
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutation in Thiamine Transporter 1 in a Family With Autosomal Dominant Diabetes

Abstract: Solute Carrier Family 19 Member 2 (SLC19A2) encodes thiamine transporter 1 (THTR1), which facilitates thiamine transport across the cell membrane. SLC19A2 homozygous mutations have been described as a cause of thiamine-responsive megaloblastic anemia (TRMA), an autosomal recessive syndrome characterized by megaloblastic anemia, diabetes, and sensorineural deafness. Here we describe a loss-of-function SLC19A2 mutation (c.A1063C: p.Lys355Gln) in a family with early-onset diabetes and mild TRMA traits transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Consistent with loss-of-function, confocal microscopy revealed that the SLC19A2 variants largely failed to traffic to the plasma membrane. Instead, intracellular puncta were observed for all three variants, suggestive of impaired transporter trafficking or recycling, a pattern that has been observed previously for mutations in SLC19A2 ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with loss-of-function, confocal microscopy revealed that the SLC19A2 variants largely failed to traffic to the plasma membrane. Instead, intracellular puncta were observed for all three variants, suggestive of impaired transporter trafficking or recycling, a pattern that has been observed previously for mutations in SLC19A2 ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 82%
“…Although genes upregulated in Mir146b- deficient macrophages are of interest as this pattern may indicate that Mir146b directly targets this/these gene(s) through canonical or non-canonical miRNA seed binding, we wanted to examine gene expression in a more global and unbiased manner so as to capture any significant changes in expression that may be related to mitochondrial dysfunction. We found several genes significantly downregulated in Mir146b cKO TGEMs, which have critical roles in both mitochondrial morphology and respiration ( Sdhd , Crtc2 , Pnpt1 , Gdf15 , Mrps28 , Mterf3 , Med30 Rnaseh1 , Slc19a2 , and Gtpbp10 ) ( Gottlieb and Tomlinson, 2005 ; Linke et al, 2017 ; Shimada et al, 2018 ; Liu et al, 2019 ; Sylvester et al, 2004 ; Taylor and Turnbull, 2007 ; Krebs et al, 2011 ; Lima et al, 2016 ; Jungtrakoon et al, 2019 ; Lavdovskaia et al, 2018 ; Figure 4A ). These findings suggest that macrophage Mir146b deficiency affects genes in the macrophage transcriptome that broadly regulate mitochondrial function and metabolism, leading to mitochondrial dysfunction and reduced metabolic capacity, similar to what is seen with aging ( Xia et al, 2016 ; van Beek et al, 2019 ; Pence and Yarbro, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…MODY can occur at different ages from childhood to early adulthood, while presenting with variable clinical features both at diagnosis and later in life [1,6]. Beyond MODY, the wide clinical spectrum of MD is substantially explained by genetic heterogeneity with various types of genetic defects in more than 30 genes, depending on the consensus of established causal genes, including some involved in rarer forms of early infancy-onset diabetes [1,6,7]. Importantly, a formal genetic diagnosis is the only way to recognize MD from common type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%